Risk of emergency admission while awaiting elective cholecystectomy - Sobolev, Boris (2003)
BACKGROUND: There is uncertainty regarding the frequency of adverse events while on a surgical waiting list. We assess the relationship between the duration of wait for cholecystectomy and the risk of emergency admission. METHODS: We analyzed time to emergency admission in a group of 761 patients who underwent cholecystectomy after being seen in clinic for biliary colic and placed on waiting lists at 2 acute care centres in Ontario, from 1997 to 2000. RESULTS: Emergency admissions due to worsening symptoms occurred in 51 patients (6.7%) waiting for elective cholecystectomy. The weekly rate of emergency admission was low during the first 19 weeks on the list, but increased almost by a factor of 3 after 20 weeks (rate ratio 2.7; 95% confidence interval 2.0–3.7). Relative to the first 4 weeks on the list, the rate was 1.6 times higher after 20 weeks, 2 times higher after 28 weeks and 7 times higher after 40 weeks. INTERPRETATION: The probability that a patient on a waiting list will be admitted for emergency cholecystectomy consistently increases with the duration of wait, particularly after 20 weeks.